2016
DOI: 10.1126/science.aaf3646
|View full text |Cite
|
Sign up to set email alerts
|

Immune modulation by MANF promotes tissue repair and regenerative success in the retina

Abstract: Regenerative therapies are limited by unfavorable environments in aging and diseased tissues. A promising strategy to improve success is to balance inflammatory and anti-inflammatory signals and enhance endogenous tissue repair mechanisms. Here, we identified a conserved immune modulatory mechanism that governs the interaction between damaged retinal cells and immune cells to promote tissue repair. In damaged retina of flies and mice, Platelet-Derived Growth Factor (PDGF)-like signaling induced Mesencephalic A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
221
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(230 citation statements)
references
References 82 publications
6
221
2
1
Order By: Relevance
“…Besides, large studies indicate that MANF can not only protect cultured nigral dopaminergic neurons and suppress cell proliferation and ERS-induced cell death, but also can affect cell morphology and size in non-neuronal cells (Petrova et al, 2004; Lindholm et al, 2007; Airavaara et al, 2009; Palgi et al, 2009; Voutilainen et al, 2009; Yu et al, 2010; Commissiong, 2012; Shen et al, 2012; Zhao et al, 2013; Yang et al, 2014; Cordero-Llana et al, 2015; Liu et al, 2015). Moreover, recently reported on science displayed that intravitreal injection recombinant MANF could promote alternative activation of innate immune cells, enhance neuroprotection and tissue repair, and improve the success of photoreceptor replacement therapies in the retina (Neves et al, 2016). These results implying that MANF may have a close relationship with the physical and pathological regulation of the retina.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, large studies indicate that MANF can not only protect cultured nigral dopaminergic neurons and suppress cell proliferation and ERS-induced cell death, but also can affect cell morphology and size in non-neuronal cells (Petrova et al, 2004; Lindholm et al, 2007; Airavaara et al, 2009; Palgi et al, 2009; Voutilainen et al, 2009; Yu et al, 2010; Commissiong, 2012; Shen et al, 2012; Zhao et al, 2013; Yang et al, 2014; Cordero-Llana et al, 2015; Liu et al, 2015). Moreover, recently reported on science displayed that intravitreal injection recombinant MANF could promote alternative activation of innate immune cells, enhance neuroprotection and tissue repair, and improve the success of photoreceptor replacement therapies in the retina (Neves et al, 2016). These results implying that MANF may have a close relationship with the physical and pathological regulation of the retina.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that in Drosophila or mouse, the damaged retina secretes Pvf-1 (platelet-derived growth factor (PDGF)- and vascular endothelial growth factor-related factor 1) and PDGF-A, respectively. These damage signals induce MANF expression in innate immune cells and MANF activation promotes a phenotype switch of macrophages from pro-inflammatory to anti-inflammatory, thereby improving tissue repair in both invertebrates and vertebrates, thus enhancing retinal regenerative therapy 60 .…”
Section: Manf Functions (Table 1) and Underlying Mechanismsmentioning
confidence: 99%
“…Microglia of the human CNS also exhibit this phenomenon, although possibly exhibiting fewer differences between polarization states (27). Importantly, acutely activated microglia are known to express neuroprotective and regenerative factors, e.g., TGFβ, IGF1, IL-10, LIF, and MANF (74,78), some of which have been shown to stimulate MG proliferation (5,6). Combined, these observations suggest that after an initial reactive response to neuronal cell death microglia may adopt an antiinflammatory phenotype to stimulate stem/ progenitor cell proliferation.…”
Section: Microglia Exhibit Several Hallmarks Of Phagocyte Activation Inmentioning
confidence: 99%
“…One promising immunomodulatory candidate is the mesencephalic astrocyte-derived neurotrophic factor (MANF). MANF was recently shown to be required for retinal repair in Drosophila and could act as a neuroprotectant, as well as promoting engraftment of transplanted progenitors/photoreceptors and improving visual recovery, in the mouse (78). Determining the role of MANF and other immunerelated factors in regulating the activation, proliferation, and differentiation of MG and their progenitors stands as a promising path to stimulating endogenous regenerative mechanisms in the human retina.…”
Section: Immunomodulator-induced Resolution Of Activated Microgliamentioning
confidence: 99%